Efficacy of In-House Quality Control Material Compared to Commercially Available Quality Control for Thyroid Hormone: Life Sciences-In House QC for Thyroid Harmone - Velu, V. Kuzhandai; Sweta, Kulkarni; Sumath, S (International Journal of Life Science and Pharma Research, 2022)
Laboratory results in clinical laboratories are being generated by automated analyzers. The constant use of commercial control materials is not economically feasible for many countries because of the non-availability or high cost of those materials. Therefore, the preparation of in-house quality control serum will be cost-effective for use in the laboratory. The commercial quality control for immunoassay is costlier and as per NABL 112 criteria, at least two levels of quality control should be run every day for a laboratory with a large sample load. To overcome this problem our study aims to evaluate the efficacy of in-house pooled serum quality control in comparison with commercial internal quality control samples in thyroid hormone tests. We prepared in-house quality control from leftover samples of subjects tested for thyroid profile after being screened for HIV, HCV, and HBsAg by pooling them together in a glass jar serum and kept in a deep freezer at -20ºC. Pooled serum was aliquot into 20 vials each containing 500 μl. Every day along with commercial internal QC, one aliquot of pooled serum was analyzed for thirty days for the following parameters: TSH, FT3, FT4. After getting thirty values for each parameter, mean, standard deviation, and coefficient of variation were calculated for both IQC commercial sample and pooled serum sample.: In-house prepared quality control material performed as well as commercial quality control for thyroid profile. Therefore, prepared in-house quality control can be a good substitute for commercial quality control for thyroid profile.